A nearly cryptic Scorpionfly, Panorpa cryptica n. sp. (Mecoptera: Panorpidae) from North America - Bicha, Wesley; Schiff, Nathan; Lancaster, Aaron; Scheffler, Brian (Zootaxa, 2015)
The first nearly cryptic species of scorpionfly from the United States, Panorpa cryptica Bicha and Schiff, n. sp., is described from northern Georgia, southwestern North Carolina and northwestern South Carolina. This insect was initially differentiated from the very similar Panorpa nebulosa Westwood by its unique cytochrome oxidase subunit I (COI) mitochondrial DNA. Habitat details, distribution, and biology are described.